(untitled) (Journal of Parents and Teachers, 2012)
This article reviews Kohlberg’s contributions to the reflection on how educating in values un a plural society. After thinking about his contributions, the author proposes 4 routes towards a moral education: the creation of affectional bonds, the search of spaces for the deliberation, the participation in activities that form values and the commitment in favor of the community.